FONTES DE ADUBAÇÃO NO DESENVOLVIMENTO DE RABANETE PROVENIENTES DE MUDA COM SUBSTRATO ALTERNATIVO - Evelyn de Souza Duarte , Clara; Leandro Silva , Maiele; Ferreira Marcelino , Adriele; Gomes Muniz , Jéssica; Ketlin Queiroz Modesto , Emilly (ANAIS DO ENIC, 2026)
-